Understanding the Potential of Sport for Promoting Physical Activity and Psychological Well-Being in Middle-Aged and Older Adults - Sivaramakrishnan, Hamsini (Curtin University, 2023)
Insufficient physical activity is considered a global public health challenge. This thesis highlights that, for middle-aged and older adults, sport participation is associated with a wide range of psychosocial benefits. Then, the thesis offers insight into the potential of walking sport programmes to promote health-enhancing physical activity in middle-aged and older adults. Recommendations are provided to promote the appeal, feasibility, and sustainability of walking sport programmes in community-based settings.